Polyvinyl Alcohol / Starch/ Glycerol/ Halloysite Nanotube Bionanocomposites for Biodegradable Packaging Applications - Abdullah, Zainab Waheed (Curtin University, 2019)
Polyvinyl alcohol/ starch/ glycerol/ halloysite nanotube bionanocomposite films were manufactured using the solution casting method. The effect of material composition and nanofiller contents on mechanical, thermal, optical, water resistance and biodegradable properties as well as the migration rates of material constituents were investigated along with the morphological structures. Modelling approaches for permeabilities have developed based on Nielsen model and Cussler model in good agreement with experimental results. Finally, prepared bionanocomposite films were confirmed to be effective food-packaging materials for lipidic and acidic fruits.